Potassium nitrate to overcome dormancy of Urochloa humidicola Comum seeds - Pereira, Thaís Soares; Jeromini, Tatiane Sanches [UNESP]; Neves, Breno Rosa [UNESP]; de Barros, Renato Téo [UNESP]; Martins, Cibele Chalita [UNESP] (Universidade Estadual de Londrina, 2021)
The main difficulty with propagating Urochloa humidicola Comum is the high percentage of seed dormancy. Thus, the objective of this study was to develop a treatment to overcome seed dormancy and promote seed germination of this species that can be applied at a large scale. This study was conducted in two stages. First, the following treatments were evaluated using one seed lot: control (without treatment), immersion in H2SO4 (98%, 36N) for 10 min, moistening the germination substrate with KNO3 (0.2%) and immersion in KNO3 at concentrations of 0%, 2%, 4%, 6%, and 8% for periods of 12, 24, 36, and 48 h, followed by drying in the shade. In the second stage, three seed lots were evaluated in all of the aforementioned treatments, except for those of immersion in 0% KNO3 and of all concentrations for 36 and 48 h. The seeds were evaluated for water content, germination, percentage of abnormal seedlings, dead and dormant seeds, first count, and average germination time. Immersion in the KNO3 solution was efficient in overcoming dormancy and promoting germination. To be used by companies, the immersion of seeds in a 4% KNO3 solution for 24 h was the most suitable treatment to overcome dormancy and promote the germination of U. humidicola Comum seeds.
Nitrato de potássio na superação da dormência de sementes de Urochloa humidicola Comum
Keywords: Forage; Germination; KNO3; Physiological potential; Quicuio grass; Urochloa humidicola